An analytical nonlinear model for plain-woven composites under off-axis loads. (15th September 2022) - Wang, Yanchao; Zhou, Yexin; Jin, Chunhua
Abstract: Woven composite is a kind of thin-wall structure that is widely used in the structural strengthening for constructions. A deep understanding of the nonlinear behavior of a woven composite is essential for its application to complex load cases. An analytical model is presented to describe the nonlinear behavior of a plain-woven composite under off-axis loads. The model is developed by combining a discrete method of a plain-woven RVE and a novel nonlinear three-phase micromechanical bridging model of a unidirectional composite. Specifically, a plain-woven RVE is firstly divided into several sub-cells. Then, each sub-cell is seen as a micro-laminate consisting of at most two unidirectional composite layers and two pure matrix layers. Further, a three-phase micromechanical bridging model is applied to simulate the nonlinear behavior of the unidirectional composite layer, where the matrix elastoplastic behavior and the interface damage are involved. The matrix deformation is described by a J2 flow rule with consideration of stress concentration factors. The interface damage is simulated by interphase with progressive stiffness degradation. The present nonlinear model is validated by comparing with experimental data of three kinds of plain-woven composites under off-axis tensile or compressive loads.